Analisis Kesalahan Penggunaan Sintaksis Pada Koran Elektronik: Sinar Indonesia Baru Edisi April 2024 - Erfriani Sekar Talenta Simangunsong; Kristin Dwi Amsari Pasaribu; Jesicha Nainggolan; Erfanintiya Siringoring; Yuliza Rahma Lubis; Mustika Wati Siregar6 (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The research carried out is useful for analyzing errors in the use of syntax found in the electronic newspaper studied, namely